The association between body mass index, primary healthcare use and morbidity in early childhood: findings from the Born In Bradford cohort study. (February 2019) - Kelly, B.; West, J.; Yang, T.C.; Mason, D.; Hasan, T.; Wright, J.
Abstract: Objectives: The objective of the article was to examine the association between body mass index (BMI), health and general practice (GP) healthcare use in early childhood. Study design: This study is a prospective cohort study. Methods: Multivariate Poisson and logistic regression models were used to explore the association between BMI and health outcomes using data from the Born In Bradford cohort study, linked to routine data capturing objective measures of BMI at age 5 years, alongside GP appointment rates, GP prescriptions and specific morbidities in the subsequent 3-year period. Results: Compared with healthy weight, children who were obese at the age of 5 years had significantly higher rates of GP appointments (incident rate ratio 1.14, 95% confidence interval [CI]: 1.06–1.23), GP prescriptions (incident rate ratio 1.15, 95% CI: 1.04–1.27), asthma (odds ratio 1.46, 95% CI: 1.21–1.77), sleep apnoea (odds ratio 2.50, 95% CI: 1.36–4.58), infections (incident rate ratio 1.19, 95% CI: 1.08–1.30), antibiotic prescriptions (incident rate ratio 1.25, 95% CI: 1.10–1.42) and accidents (incident rate ratio 1.20, 95% CI: 1.01–1.42) in the subsequent 3 years. Underweight children were found to have higher rates of GP appointments (incident rate ratio 1.25, 95% CI: 1.04–1.52), but there were no differences between overweight and healthy weight children. Conclusions: Childhood obesity was found to be associated with increased primary healthcare use and a range of poorer health outcomes at the age of 8 years, underlining the importance of reducing childhood obesity in early childhood. Highlights: Childhood obesity is associated with poor health and increased healthcare use. Compared with healthy weight children, obese children have more general practice appointments and prescriptions in early childhood. The impact of obesity on health and healthcare use is evident at a very early age.